2016
DOI: 10.1021/acs.analchem.6b02849
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Oxygen and pH Inside Microfluidic Devices Using Core–Shell Nanosensors

Abstract: A powerful online analysis setup for the simultaneous detection of oxygen and pH is presented. It features core-shell nanosensors, which enable contactless and inexpensive read-out using adapted oxygen meters via modified dual lifetime referencing in the frequency domain (phase shift measurements). Lipophilic indicator dyes were incorporated into core-shell structured poly(styrene-block-vinylpyrrolidone) nanoparticles (average diameter = 180 nm) yielding oxygen nanosensors and pH nanosensors by applying differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
2
36
0
2
Order By: Relevance
“…The synthesis of the oxygen‐sensitive particles as well as their characterization and calibration were described in previous works (Ehgartner, J., Strobl, et al, 2016; Ehgartner, Sulzer, et al, 2016). Oxygen monitoring was carried out at a sampling frequency of 1 Hz using a FireStingO2 optical oxygen meter (Pyroscience, Germany) connected to optical fibers (length 1 m, outer diameter 2.2 mm, fiber diameter 1 mm; Sticker et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of the oxygen‐sensitive particles as well as their characterization and calibration were described in previous works (Ehgartner, J., Strobl, et al, 2016; Ehgartner, Sulzer, et al, 2016). Oxygen monitoring was carried out at a sampling frequency of 1 Hz using a FireStingO2 optical oxygen meter (Pyroscience, Germany) connected to optical fibers (length 1 m, outer diameter 2.2 mm, fiber diameter 1 mm; Sticker et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Electrochemical biosensors embedded inside microfluidic chips facilitate multiplexed sensing of different parameters such as pH, oxygen, glucose, lactate, and chloride (Ehgartner et al, 2016). In addition, microfluidic centrifugal technology has enabled miniaturization of typical laboratory processes such as blood plasma separation (Haeberle et al, 2006) and enzymelinked immunosorbent assay (Lai et al, 2004).…”
Section: Multiplexed Sensingmentioning
confidence: 99%
“…Even multiple parameters in one sensor are now possible. 7 The quantification of key variables of biotechnological processes is thus feasible with optical sensors alone. Furthermore, not only have new analytes been added, there is now also a range of novel dyes and sensor matrices, and with it a host of sensor preparation and integration methods.…”
Section: Marco Marquesmentioning
confidence: 99%
“…Ehgartner et al (2016) 7 showed that it is possible to simultaneously monitor oxygen and pH using core-shell nanosensors in a microfluidic flow system. For this purpose lipophilic oxygen and pH nanoparticles were embedded into polyIJstyrene-block-vinylpyrrolidone) nanoparticles.…”
Section: F Multi-parameter Online Monitoringmentioning
confidence: 99%